An unusual case of comedones. (11th May 2022) - Haywood, Sophia; Barker, Ruth; Blakeway‐Manning, Elizabeth; Walton, Shernaz
Abstract : We present the case of a 71‐year‐old woman with widespread comedones since adolescence. Histological examination revealed branching hyperpigmented rete ridges and cystically dilated follicular infundibulum containing laminated keratinous debris. We explore the differential diagnosis in the context of other reticulate hyperpigmentation disorders.